Four good days [videorecording (DVD)] - García, Rodrigo, 1959-; García, Rodrigo, 1959-; García, Rodrigo, 1959-; Close, Glenn, 1947-; Kunis, Mila, 1983-; Root, Stephen; Saslow, Eli (Vertical Entertainment, 2021)
After leaving a detox clinic, a young addict must stay clean while spending the next four days with her mother.